2018
DOI: 10.7577/njsr.2235
|View full text |Cite
|
Sign up to set email alerts
|

What Works? Family Influences on Occupational Aspirations among Descendants of Middle Eastern Immigrants on the Swedish Labour Market

Abstract: In this article, we examine family influences on occupational aspirations among employed descendants of Middle Eastern immigrants. Using a qualitative approach, we conducted 21 semi-structured interviews with native-born descendants of Middle Eastern immigrants. We present and analyse their interpretations of their parents’ experiences and living conditions before, during and after migration and demonstrate how these interpretations shaped their own occupational aspirations. We discuss parents’ high expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Previous research has shown the importance of employment for social inclusion and integration of migrants (e.g., Aslan et al 2018;van Riemsdijk et al 2016), and public officials can play an important role in facilitating the process towards gaining employment (Aslan et al 2019;Eggenhofer-Rehart et al 2018;Pajic et al 2018). An individual's perception of their employment opportunities is influenced by a number of aspects, among them ascriptions of employability, suggested guidance and information provided by government officials, Public Employment Service representatives, and recruitment agents.…”
Section: Aims and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown the importance of employment for social inclusion and integration of migrants (e.g., Aslan et al 2018;van Riemsdijk et al 2016), and public officials can play an important role in facilitating the process towards gaining employment (Aslan et al 2019;Eggenhofer-Rehart et al 2018;Pajic et al 2018). An individual's perception of their employment opportunities is influenced by a number of aspects, among them ascriptions of employability, suggested guidance and information provided by government officials, Public Employment Service representatives, and recruitment agents.…”
Section: Aims and Research Questionsmentioning
confidence: 99%
“…This process is far from an easy endeavour (e.g., Diedrich 2017). As previous research has pointed out, participation in the labour market is an important component of integration and social inclusion (e.g., Aslan et al 2018;van Riemsdijk et al 2016). In addition, paid employment is the main road towards securing permanent residency (SFS 2016(SFS :752 2016.…”
Section: Introductionmentioning
confidence: 99%